Heterogenous Traffic Performances on Local Multipoint Distribution Service System in Rainy Environment - Naemah Mubarakah; Suherman Suherman; Yulianta Siregar; Arman Sani (Universitas Ahmad Dahlan, 2015)
Local multipoint distribution service (LMDS) system provides high bitrates services up to 40 Mbps operating in millimeter bands. The radio system can be employed to serve heterogenous traffics in any applications such as video surveillance, public internet hotspots and other services. However, the implementation in tropical area faces transmission problems which degrade signal reception, such as heavy rain. This paper examines the performance of heterogenous traffics in LMDS in a rainy environment. Some techniques to tackle rain ploblems were implemented and the effects were assesed. It was proven that PHY and MAC layers contribute to performances enhancement on rainy environment as long as the system uses the suitable scheduler. A packet-based scheduler was proposed by considering packet impact on quality. The results showed that the proposed technique is able to improve video performance about 0.02% over the maximum signal to noise (mSNR) scheduler, maintain voice decoding rate as well as the priority fair (PF) scheduler and increase data decodibility 0.2%.